The Perceptions of Diabetes Lay Educators Working with Migrant Farmworkers - Loretta Heuer; Cheryl Lausch; Jane Bergland (Rural Nurse Organization; Binghamton University, 2012)
Diabetic medical care for Hispanic migrant farmworkers has been hard to obtain due to the lack of continuity in health care and limited access to services. These factors have led to either gaps or duplications of services for these clients. Migrant Health Service, Inc. (MHSI) Diabetes Program staff addressed these issues through the development of a Diabetes Lay Educator Program. This qualitative study explored the lived experience of Diabetes Lay Educators (DLEs) as they worked with migrant farmworkers traveling between multiple states. The sample consisted of seven female participants who migrated from southern Texas. Four main themes emerged: Understanding the lifestyle; Self-managing diabetes when traveling; Roles of the Diabetes Lay Educators; and Access to health care services. The utilization of DLEs is an effective way to provide health care and education to this migrant population.